Internal Communication and Internal Marketing as elements of Integrated Marketing Communication (IMC) in Public Universities - Panigyrakis, George G.; Kyriacou, Evdoxia (My University, 2020)
This study examines the relationship between the internal communication and nine dimensions of Internal Marketing and their interconnection to shape the conditions for the job satisfaction. The paper utilizes the mixed method. Data were collected from six Public Universities in Greece and in Cyprus. Findings are presented and results are discussed.
Keywords: Internal communication; Integrated marketing communication; Internal marketing; Value system; Universities